An In-Vitro Study of the Antibacterial Efficacy of Cavity Liners Against Streptococcus Mutans and Lactobacillus Casei - N kazeroonizadeh; M Kazemian; P Mirzakoochaki brojen (Islamic Azad University, 2017)
Background and aim: The main factor that influences the durability of dental restorations is secondary caries. Antibacterial activity of dental materials is important from the clinical aspect, as it might inhibit recurrent caries. The aim of the present study was to compare the antibacterial activity of four fluoride-releasing dental cavity liners against Streptococcus mutans (S. mutans) and Lactobacillus casei (L. casei). Materials and methods: In this experimental in-vitro study, the agar diffusion test was used to compare the antibacterial efficacy of four dental cavity liners against S. mutans and L. casei. Indicator strains of S. mutans (ATCC35668) and L. casei (ATCC393) were obtained in the form of lyophilized culture. They were grown separately in 15 ml of Brain Heart Infusion (BHI) agar at 37 °C for 48 hours. Antibacterial activities of Ionobond (VOCO), Ionoseal (VOCO), Ionosit (DMG), and Vitrebond (3M) dental cavity liners were evaluated at 24 and 48 hours and at 7 days by measuring the diameter of the inhibition zone in millimeters (mm). Data were collected and analyzed using the repeated measure ANOVA and T-test. The level of significance was set at p<0.05. Results: The antibacterial efficacy of the four studied dental cavity liners differed at different time intervals (p<0.001), but there were no statically significant differences in the antibacterial activity against the two bacteria types (p=0.342), or between the four types of dental cavity liners (p=0.07). Conclusion: According to the results of the present research, the antibacterial activities of Ionobond, Ionoseal, Ionosit and Vitrebond dental cavity liners were not significantly different and decreased over time.